Gender-Based Differences in Physical Activity and Sports Habits among 8-12-year-old Schoolchildren in Gipuzkoa - Irantzu Ibañez; Aitor Iturricastillo; Oidui Usabiaga; Aduna Badiola-Lekue (Journal of Sport and Health Research, 2026)
Objectives: To analyze gender differences in physical activity and sport (PAS) habits among schoolchildren aged 8 to 12 years in the province of Gipuzkoa, Spain. Methods: A total of 2,817 schoolchildren (49.6% girls) completed the validated multidimensional Physical Activity and Sports Habits Questionnaire. Gender differences were analyzed using Pearson's Chi-Square of Independence and Z-tests. The effect size was calculated using Cramer's V. Results: Significant gender differences were found in PA levels, screen time, sleep duration and participation in organized and non-organized PAS. Boys showed higher engagement in group and competitive sports and and girls reported lower screen time and longer sleep durations. No gender differences were found in motivational or environmental factors. Conclusions: Gender disparities in PAS habits in childhood should be considered when designing tailored interventions and gender-responsive public policies to promote PAS for children.